(untitled) (Islamic Sciences Journal, 2024)
Philon Alexanderi was one of the first Jewish philosophers, born in (20 B.C.) in a notable Jewish family of a distinguished position in the Alexandrian Jewish community. He studied philosophy and was strongly influenced by the views of Plato that he was called Plato of the Jews. Accordingly, he interpreted the Torah metaphorically, by reconciling philosophy and religion. He made many travels, the most important of which was that to Emperor Caligula in Rome to convince him not to erect idols in Jewish temples. In our research, we present Philon’s thought about the existence of Allah Al-Mighty, His nature, what He is, and His attributes. The most prominent thing in his philosophy about Allah Al-Mighty is that he said monotheism, contrary to the doctrine of pluralism that was prevalent at the time, as he derived the saying of monotheism from his Jewish faith, but he contradicted the people of his religion for he believed that Allah Al-Mighty is not only the God of the Children of Israel, rather, He is the God of the whole world. Added to that is his saying of -Logos- the word of Allah Al-Mighty which came based on his theory of God, whereby he saw that God cannot create evil – he was influenced by Plato - but rather created the Logos and entrusted him with the creation of matter that Philon considered a source of evil and sins. The Logos doctrine later affected the Christian religion, but it was not accepted by the Jewish rabbis, as some considered it as a departure from the Jewish faith, and that Philon was a Christian in secret. Philon died around the year 50 AD.